1953
DOI: 10.6013/jbrewsocjapan1915.48.316
|View full text |Cite
|
Sign up to set email alerts
|

On Restoring the Sporulation Ability of Sakê Yeasts

Abstract: It is well known that the yeast loses its superior quality as well as sporulation ability, when its pure culture is transplanted or its specimen is stored for many years. The Society of Brewing, Japan, established in the Governmental Brewing Experimental Station, has distributed a large number of superior pure yeast cultures for use in brewing sake since 1906. The most excellent and most widely distributed sake yeast, No. 6 of this Society,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1954
1954
1960
1960

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Tremaine & Miller (1954) found that maximal sporulation, and the production of the highest number of 4-spored asci, depended on the presence of a full complement of B vitamins in the presporulation medium; under these conditions, no advantage accrued from the addition of vitamins to the sporulation medium, with the exoeption of pantothenate which, it was claimed, gave inoreaaed yields of Thermolabile substances such as enzymes are destroyed when growth media are heat sterilized. Tsukahara & Yamada (1953) claimed that sporulating ability in sake yeasts can be restored by serial transfer in raw koji extract sterilized by filtration instead of heat. According to these authors, enzymes and other thermolabile substances in the koji extract were necessary for sporulation.…”
mentioning
confidence: 99%
“…Tremaine & Miller (1954) found that maximal sporulation, and the production of the highest number of 4-spored asci, depended on the presence of a full complement of B vitamins in the presporulation medium; under these conditions, no advantage accrued from the addition of vitamins to the sporulation medium, with the exoeption of pantothenate which, it was claimed, gave inoreaaed yields of Thermolabile substances such as enzymes are destroyed when growth media are heat sterilized. Tsukahara & Yamada (1953) claimed that sporulating ability in sake yeasts can be restored by serial transfer in raw koji extract sterilized by filtration instead of heat. According to these authors, enzymes and other thermolabile substances in the koji extract were necessary for sporulation.…”
mentioning
confidence: 99%